Effect of valve opening shapes on the performance of a single‐stage Gifford‐McMahon cryocooler. Issue 3 (27th October 2019) - Panda, Debashis; Satapathy, Ashok K.; Sarangi, Sunil K.
Abstract : In this work, the effect of the triangular and Gaussian‐shaped opening of the rotary valve (ie, the valve timing diagram of high‐pressure and low‐pressure valves) on the performance of a single‐stage Gifford‐McMahon (GM) cryorefrigerator is numerically investigated. In addition, the effect of waiting time of the rotary valve on its cooling power and coefficient of performance is studied for both types of opening shapes. The governing equations representing the fluid flow and heat transfer behaviors of the refrigerator are solved by using an implicit finite‐volume discretization method. The model considers both primary and secondary loss mechanisms. The developed model is first validated with the published results on GM cryorefrigerators. A very good agreement appears among them. It is observed that no significant change can be appreciated in the cooling power between 40° to 90° of waiting time for both types of opening shapes. On the other hand, in‐between 1° to 40° of waiting time, the cooling power of the Gaussian‐shaped opening of the rotary valve is higher than the one of the triangular opening.